Childhood abuse and neglect in relation to the presence and persistence of psychotic and depressive symptomatology. Issue 7 (17th July 2014) - van Dam, D. S.; van Nierop, M.; Viechtbauer, W.; Velthorst, E.; van Winkel, R.; ,; Bruggeman, R.; Cahn, W.; de Haan, L.; Kahn, R. S.; Meijer, C. J.; Myin-Germeys, I.; et al.
Abstract : Background: The association between childhood trauma and psychotic and depressive symptomatology is well established. However, less is known about the specificity and course of these symptoms in relation to childhood trauma. Method: In a large sample ( n = 2765) of patients with psychosis ( n = 1119), their siblings ( n = 1057) and controls ( n = 589), multivariate (mixed-effects) regression analyses with multiple outcomes were performed to examine the association between childhood trauma and psychotic and depressive symptomatology over a 3-year period. Results: A dose–response relationship was found between childhood trauma and psychosis. Abuse was more strongly associated with positive symptoms than with negative symptoms whereas the strength of the associations between neglect and positive and negative symptoms was comparable. In patients, similar associations between childhood trauma and psychotic or depressive symptoms were found, and in siblings and controls, stronger associations were found between trauma and depressive symptomatology. Childhood trauma was not related to a differential course of symptoms over a 3-year time period. Conclusions: In congruence with earlier work, our findings suggest that childhood trauma, and abuse in particular, is associated with (subthreshold) psychosis. However, childhood trauma does not seem to be associated with a differential course of symptoms, nor does it uniquely heighten the chance of developing (subthreshold) psychotic symptomatology. Our results indicate that trauma may instead contribute to a shared vulnerability for psychotic and depressive symptoms.